The undoing of violet claybourne eaudiobook A novel. - Critchley, Emily (Recorded Books, 2025)
"Artful, gothic-tinged ... an immersive, chilling treat for suspense fans."— Publishers Weekly For fans of Sarah Penner and The Foundling comes a slow-burn gothic mystery following Gillian, a young girl enthralled by the enigmatic Claybourne sisters, their house at Thornleigh Hall, and the tragedy that binds them together for good. To become a Claybourne girl, she'll have to betray one first. 1938. Gillian Larking, lonely and away at boarding school, is used to going unnoticed. But then she meets Violet Claybourne, her vibrant roommate who takes Gilly under her wing. Violet is unlike anyone Gilly has ever met, and she regales Gilly with tales of her grand family estate and her two elegant sisters. Gilly is soon entranced by stories of the Claybournes, so when Violet invites Gilly to meet her family at Thornleigh Hall, she can't believe her luck. But Gilly soon finds that behind the grand façade of Thornleigh Hall, darkness lurks. Dazzled by the crumbling manor and Violet's enigmatic sisters, Gilly settles into the estate. But when a horrible accident strikes on the grounds, she is ensnared in a web of the sisters' making, forced to make a choice that will change the course of her life forever. Because the Claybourne girls know how to keep secrets, even at the cost of one of their own. With ensnaring prose and layers of friendship, privilege, mental health, and more, The Undoing of Violet Claybourne is a poignant book club read with characters you won't soon forget.